Effectiveness of degradable polymer film in the management of severe or moderate intrauterine adhesions (PREG-2): a randomized, double-blind, multicenter, stratified, superiority trial - Fernandez, Hervé; Miquel, Laura; Sroussi, Jérémy; Weyers, Steven; Munmany, Meritxell; Luo, Xiping; Kovar, Petr; Wang, Yue; Zizolfi, Brunella; Surbone, Anna; Delporte, Victoire; Moratalla, Enrique; et al. (Fertility and sterility, 2024)
OBJECTIVE: To study the effectiveness of a new intrauterine degradable polymer film (Womed Leaf) in the management of moderate to severe intrauterine adhesions (IUA). DESIGN: PREG-2 study was a multicenter, double-blind, randomized, controlled, stratified, two-arm superiority clinical trial conducted in 16 centers in seven countries. SETTING: Not applicable. PATIENT(S): Patients ≥18 years scheduled for hysteroscopic adhesiolysis because of symptomatic severe or moderate adhesions (according to American Fertility Society [AFS] IUA score) were considered eligible for the study. INTERVENTION(S): After adhesiolysis, patients were randomized at a 1:1 ratio to either have a Womed Leaf film inserted (intervention group) or not (control group). MAIN OUTCOME MEASURE(S): The primary effectiveness endpoint of the study was the change in AFS IUA score on second-look hysteroscopy (SLH), assessed by an independent evaluator, and compared with baseline. Information on the rate of no IUA and responder rate was collected as secondary effectiveness outcomes, while reported adverse events and patient-reported outcomes as safety and tolerability measures. RESULT(S): Between October 26, 2021, and September 28, 2023, a total of 160 women were randomized (Womed Leaf: n = 75 and controls: n = 85). The reduction in IUA AFS score on SLH was significantly higher in the intervention compared with the control group (mean 5.2 ± 2.8 vs. 4.2 ± 3.2). Similarly, the absence of adhesions on SLH was significantly higher in the intervention group (41% vs. 24%; odds ratio, 2.44; confidence interval, 1.161-5.116). None of the reported adverse events were serious or considered related to the device. CONCLUSION(S): Womed Leaf is effective and safe in the management of symptomatic severe or moderate IUAs. CLINICAL TRIAL REGISTRATION NUMBER: Clinicaltrials.gov identifier: NCT04963179.
Keywords: dospělí; Female; vstřebatelné implantáty; Tissue Adhesions; Adult; výsledek terapie; ženské pohlaví; Uterine Diseases; Polymers; lidé; hysteroskopie; dvojitá slepá metoda; Treatment Outcome; stupeň závažnosti nemoci; Absorbable Implants; adheze tkání; Double-Blind Method; polymery; nemoci dělohy; Hysteroscopy; Severity of Illness Index; Humans